An African Perspective on Surrogacy and the Justification of Motherhood - Aina, Akande Michael (Bangladesh Journal of Bioethics, 2017)
Surrogacy as a practice is supported by science, technology, morality and legality. It follows that the issues concerning it cut across all facets of life. And different arguments have being advanced for and against this practice. The belief espouse in this paper is that one cannot discuss successfully the moral, the science or the legality of surrogacy without delving into the cultural question of who is a mother. In other words, it is possible to have simple scientific and legal understandings of the practice and still disagree on the cultural level because of its stronger emotional appeal. The purpose of this work is to expose the Yoruba-African religio-cultural beliefs that have bearing on the understanding of motherhood or ownership of a child. This will be done through a critical analysis of Yoruba cultural beliefs about personhood and the metaphysical underpinning between birth and the ontology of life itself. Theargument here is that given some Yoruba ontological belief about life, motherhood and personhood it may be difficult for the products of surrogacy to fit-in into the society in terms of personal and social development. This work goes further to recommend that cultural beliefs should be taking into consideration when making laws to guide surrogacy in order to avoid conflict between the mothers and the child.